Respuesta :
so hmmm x²+6x+8=0
alrite.. let's do some grouping now
( x² + 6x + [?]²) + 8 = 0
notice above, we have a missing fellow in order to get a perfect square trinomial... hmm who would that be?
let's take a peek at the middle guy of the trinomial.. 6x.. hmmm let's factor it, 2*3*x, wait a minute! 2 * 3 * x... we already have x² on the left-side, since the middle term is just 2 * the square root of the other two terms, that means that the guy on the right, our missing guy must be "3"
alrite, let's add 3² then, however, bear in mind that, all we're doing is borrowing from our very good friend Mr Zero, 0
so if we add 3², we also have to subtract 3², let's do so
(x² + 6x +3² - 3²) + 8 = 0
(x² + 6x +3²) + 8 - 3² = 0
(x+3)²=3² - 8
(x+3)² = 1
alrite.. let's do some grouping now
( x² + 6x + [?]²) + 8 = 0
notice above, we have a missing fellow in order to get a perfect square trinomial... hmm who would that be?
let's take a peek at the middle guy of the trinomial.. 6x.. hmmm let's factor it, 2*3*x, wait a minute! 2 * 3 * x... we already have x² on the left-side, since the middle term is just 2 * the square root of the other two terms, that means that the guy on the right, our missing guy must be "3"
alrite, let's add 3² then, however, bear in mind that, all we're doing is borrowing from our very good friend Mr Zero, 0
so if we add 3², we also have to subtract 3², let's do so
(x² + 6x +3² - 3²) + 8 = 0
(x² + 6x +3²) + 8 - 3² = 0
(x+3)²=3² - 8
(x+3)² = 1
Step 1x2 + 6x + 8 + 1 = 0 + 1
Step 2x2 + 6x + 9 = 1
Step 3(x + 3)2 = 1
Your answer is (x +3)2 = 1
Hope I helped <3
Step 2x2 + 6x + 9 = 1
Step 3(x + 3)2 = 1
Your answer is (x +3)2 = 1
Hope I helped <3